When the Past is Far from Dead: How Ongoing Consequences of Genocides Committed by the Ingroup Impact Collective Guilt. (7th March 2013) - Imhoff, Roland; Wohl, Michael J. A.; Erb, Hans‐Peter
<x xml:space="preserve">Abstract</x> In two experimental studies, we examined how the ongoing negative consequences for victims of genocides committed by Germans influence the acceptance of collective guilt in young Germans living today. Experiment 1 showed that collective guilt is undermined when the genocide against the Herero people in Namibia is framed as having no impact on contemporary tribe members. The downstream consequence was reduced reparatory intentions. Extending these results, Experiment 2 replicated these findings in the context of Nazi crimes against Jews. In addition, we manipulated to what degree the compliance with the Holocaust was perceived as intentional, a widely debated issue in Holocaust studies. In line with predictions derived from attribution theory, collective guilt and reparatory intentions were particularly prevalent when the Holocaust was explained as the result of deliberate intentions of the ingroup. Implications for ingroup responses to historical harmdoing are discussed.